2018
DOI: 10.25165/j.ijabe.20181103.3717
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization and test for a pendulum suspension of the crop sprayer boom in dynamic conditions based on a six DOF motion simulator

Abstract: Spray deposit distribution from a field sprayer is mainly affected by the boom movements when the tractor is driven over a rough soil surface, the pendulum suspension that used to reduce and control the movement of spray boom by isolating the boom from vibrations of the tractor will directly enhance uniform deposition of chemicals. However, how to match the parameters of the suspension with the properties of the boom is the key problem. The dynamic rigid-flexible coupling model of the virtual prototype of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Although the agricultural pests and diseases can be controlled effectively by chemical control methods, the extensive use and low utilization of plant protection products (PPPs) arose as the side effects of chemical control [4][5][6] . In order to cope with high-risk pests and diseases, the annual global use of PPPs in pests and diseases was more than 3 billion kg [7] .…”
Section: Introduction mentioning
confidence: 99%
“…Although the agricultural pests and diseases can be controlled effectively by chemical control methods, the extensive use and low utilization of plant protection products (PPPs) arose as the side effects of chemical control [4][5][6] . In order to cope with high-risk pests and diseases, the annual global use of PPPs in pests and diseases was more than 3 billion kg [7] .…”
Section: Introduction mentioning
confidence: 99%
“…Lots of scholars have studied on the simulation-based optimization approach [9][10][11][12] . In addition to the inventory research, many scholars have used simulation-based optimization approach to solve a variety of practical problems [21][22][23][24][25] in recent years. In this paper, the Flexsim software and improved particle swarm optimization algorithm are used to establish the simulation-based optimization model.…”
Section: Mathematical Model Of Multi-echelon Inventory System Of Fresmentioning
confidence: 99%
“…Previous works [18][19][20][21][22][23][24] showed that the greatest effect on undesirable spray boom motion is due to the roll motion of spray vehicle, as it travels on undulating terrain. In order to reduce the unevenness in spray deposit, the active suspension should act as a system that isolating the boom from vibrations of spray vehicle.…”
Section: Sinusoidal Interference Condition Testmentioning
confidence: 99%
“…Several investigators have studied a number of boom suspension techniques, both theoretically and experimentally [19][20][21][22] . In these works, different control methods such as proportional (P), proportional-integral (PI) and H∞ control theory have been tried to control the motion of boom [23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%